2022
DOI: 10.3389/fphar.2022.898360
|View full text |Cite
|
Sign up to set email alerts
|

Zi Shen Wan Fang Attenuates Neuroinflammation and Cognitive Function Via Remodeling the Gut Microbiota in Diabetes-Induced Cognitive Impairment Mice

Abstract: Background: Cognitive dysfunction is a critical complication of diabetes mellitus, and there are still no clinically approved drugs. Zi Shen Wan Fang (ZSWF) is an optimized prescription composed of Anemarrhenae Rhizoma, Phellodendri Chinensis Cortex, and Cistanches Herba. The purpose of this study is to investigate the effect of ZSWF on DCI and explore its mechanism from the perspective of maintaining intestinal microbial homeostasis in order to find an effective prescription for treating DCI.Methods: The diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Anemarrhenae Rhizoma/Phellodendri Chinensis Cortex herb pair, diabetes, Nrf2/Keap1 signalling, osteoporosis, pyroptosis as diabetic nephropathy and diabetes-induced cognitive impairment, through the reduction in Nlrp3 and Caspase1 levels. 26,27 Based on the above findings, it is reasonable to speculate that AR/PPC herb pair may yield a similar role in attenuating osteoblast pyroptosis and mitigating the development of DOP.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Anemarrhenae Rhizoma/Phellodendri Chinensis Cortex herb pair, diabetes, Nrf2/Keap1 signalling, osteoporosis, pyroptosis as diabetic nephropathy and diabetes-induced cognitive impairment, through the reduction in Nlrp3 and Caspase1 levels. 26,27 Based on the above findings, it is reasonable to speculate that AR/PPC herb pair may yield a similar role in attenuating osteoblast pyroptosis and mitigating the development of DOP.…”
Section: Introductionmentioning
confidence: 84%
“…5 The AR/PCC is a traditional Chinese herbal pair that has been widely utilized for the management of DM. 9,27,45 Importantly, both our latest discoveries and other studies using zebrafish or rodent DM models have demonstrated the effective attenuation of osteoporotic phenotypes by AR/PCC or certain AR/PCC-derived compounds. [8][9][10][11] Based on these findings, we hypothesized that AR/PCC exhibits beneficial properties against DOP progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Hyperglycemia has been shown to result in intestinal barrier dysfunction, 21 and a study in mice fed a high-fat diet combined with intraperitoneal injections of streptozotocin confirmed that diabetes could affect intestinal permeability. 50 Our study demonstrated that db/db mice exhibited impaired intestinal barrier function. After the administration of PYR, intestinal ultrastructural morphology and TJ protein expression improved.…”
Section: Discussionmentioning
confidence: 56%
“…This low‐grade chronic inflammation, which is triggered by the influx of bacterial component LPS and inflammatory bacterial fragments into the circulation through a defective gut barrier, has significant knock‐on effects on obesity, insulin resistance, and multiple organ failure 49 . Hyperglycemia has been shown to result in intestinal barrier dysfunction, 21 and a study in mice fed a high‐fat diet combined with intraperitoneal injections of streptozotocin confirmed that diabetes could affect intestinal permeability 50 . Our study demonstrated that db/db mice exhibited impaired intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%